Object Pragmatics: Culture and Communication - the Bases for Early Cognitive Development - Rodríguez, Cintia; Basilio, Marisol; Cárdenas, Karina; Cavalcante, Sílvia; Moreno-Núñez, Ana; Palacios, Pedro; Yuste, Noemí (The Cambridge Handbook of Sociocultural Psychology, 2023)
[Resumen no disponible]
Keywords: culture; communication; early cognitive developmentc; Scopus(2)